UMP Campus Pantry – free food hub for students - Nor Salwana, Mohammad Idris (2019)
In line with the aspiration of Domestic Trade and Consumerism Ministry (KPDNHEP) in implementing the Food Bank Malaysia programme in public universities, Universiti Malaysia Pahang (UMP) raised to the occasion by having its own UMP Campus Pantry, offering food and other basic necessities to students. The programme was established on April 16, 2019.